Odpowiedzi

2010-03-23T17:59:28+01:00
A)6x =3/:6
x= 0,5

b)-3x=7/:(-3)
x= -2i1/3

c)2x=1/5/:2
x= 0,1

d)1,2x=4,8/:1,2
x= 4

e)1/3x=3/:1/3
x= 9

f)-3/5x=-5/:(-3/5)
x= 25/3

g)3/4x=-4/9/:3/4
x= 2/3

h)0,1x=-7/:0,1
x= -70



2010-03-23T17:59:37+01:00
A)6x =3 /:6
x=3/6
x=1/3
b)-3x=7 :-3
x=-7/3
x=-2 1/3
c)2x=1/5 /*1/2
x=1/10
d)1,2x=4,8
12/10x=48/10 /*10/12
x=4
e)1/3x=3 /*3
x=9
f)-3/5x=-5 /*5/3
x=25/3
x=8 1/3

g)3/4x=-4/9 /*4/3
x=-16/27

h)0,1x=-7
x=-70
2010-03-23T18:02:37+01:00
A)
6x=3 |÷6
x = ½
b)
-3x=7 |÷(-3)
x= - 7/3
x = - 2 i1/3
c)
2x=⅕ |÷2
x=⅕ ÷ 2
x= ⅕ * ½
x=1/10
d)
1,2x=4,8 |/1,2
x = 4
f)
-3/5 x = -5|* (-5)
3x=25|/3
x = 25/3
x=8⅓
e)
1/3x=3|*3
x=9
g)
3/4x=-4/9|*4
3x= - 16/9|÷3
x= -16/9 ÷ 3/1
x= -16/9 * 1/3
x= -16/27
h)
0,1x=-7 |*10
x = -70